Emotion, character, and responsibility - Sabini, John 1947-; Silver, Maury 1944-; Oxford scholarship online (Online service). (New York Oxford University Press, 1998)
Written in a jargon-free style and of interest to both academics and the lay reader, this collection of essays explores why emotions are important in the conception of a person's character and in their own conception of self.
Includes bibliographical references and index.
Keywords: Emotions; Character; Responsibility; Electronic books